Responsabilidad del estado en la garantía de los derechos educativos de los niños con discapacidad intelectual en Guayaquil - Quimi Murillo, Katherine Nicole (2025)
The Ecuadorian Constitution enshrines education as a fundamental right of every individual, with the responsibility of ensuring access and quality for all children, including those with intellectual disabilities. However, despite the existence of regulations aimed at protecting these rights, the reality reflects a different scenario, where there is a deficiency in the implementation of inclusive policies. This research will take as its starting point the protection and enforcement of the provisions established by the Ministry of Education, considering that this population currently requires greater protection. Active participation in the rights of children with disabilities is essential to strengthening inclusion and their autonomy in different environments. The purpose of this thesis is to contribute to improving the Ministry of Education’s involvement in inclusive education, programs, health measures, and previously established practices.